Comparative analysis of autologous platelet-rich plasma and topical insulin injections on wound healing outcomes in patients with diabetic foot ulcers: a retrospective study - Jaganathan, Sridhar; Sangeethapriya, Dharaneesh Selvaraja; Reddy, Baddam Nikhil (International Surgery Journal, 2025)
Background: Diabetes mellitus is a chronic condition leading to high blood sugar due to pancreatic dysfunction, insulin resistance, or decreased insulin production. Among diabetics, 4–10% develop diabetic foot ulcers (DFUs), with elderly patients at higher risk. A cost-effective and efficient treatment approach is needed for prolonged ulcers. Insulin promotes wound healing through molecular mechanisms involving AKT and ERK pathways. Platelet-rich plasma (PRP) contains high concentrations of platelets and growth factors that accelerate healing. Methods: A randomized clinical study of 100 patients with post-debridement DFUs (<10×10 cm²) divided into two groups: Group A received PRP injections, and Group B received topical insulin. Wound healing was assessed on days 3, 7, 14, and 21 based on ulcer size reduction, granulation tissue formation, and need for further intervention. Data were analyzed using Statistical Software, with p<0.05 considered significant. Results: The PRP group had a mean age of 57.18 years, and the Topical Insulin group, 56.28 years (p=0.36). PRP showed superior granulation tissue formation (59.88±1.30 vs. 44.48±1.71 at day 21), shorter hospital stays (21.34 vs. 30.94 days, p=0.0001), and fewer re-interventions (36% vs. 62%, p=0.009). Conclusion: The findings consistently show that PRP outperforms Topical Insulin in key areas such as reducing ulcer size, promoting granulation tissue growth, shortening hospital stays, reduced need for re-interventions.